Gagasan Baru Tentang Wahyu: Ke Arah Dialog Kritis Antaragama (Membangun Masyarakat Kitab Bersama Mohammed Arkoun) - Anas, Mohamad (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2019)
During this time, the conversation about revelation in monotheistic religions (Jews-Christians-Islam) has always been dominated by dogma which leads to subjetivity and truth claims. As a result, discussions concerning the dogmas of each religion do not find a meeting point or are unlikely to be able to enrich even the insight. This happens because a layer of understanding has become a dogma and is believed to be a truth that cannot be criticized. In that context, Arkoen conducted criticism by using contemporary methods and approaches (history, thought and language) to see the condition of the book society which had been dominated by an understanding of revelation that was very polemic. Through a contemporary social science approach, Arkoun encourages the birth of a society that promotes critical rationalism. This community must understand the position of revelation from the first level to the fourth level. Arkoun also encouraged the realization of an open society, all opened and dialogue without feeling overwhelmed by dominant understanding and classical history. Book community dialogue is still limited, followed by three monotheistic religions, but efforts to realize this society must fulfill several basic prerequisites. First, make an effort to rethink old concepts of religion and society towards an era of new thinking based on historical solidarity and social integration. Secondly, reforming thought from exclusive theological thinking towards radical criticism without concessions to